IDENTIFIKASI KONTEN, KEGUNAAN, DAN FITUR TAMBAHAN TERHADAP MINAT REKRUTMEN ONLINE - Fuad Arif Rahman; Yulinda Tarigan; Rakhmad Dani, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The main objective of this research is to identify content, usability, additional features on online recruitment interest with a case study on university fresh graduate in Batam City. This research approach uses a quantitative approach and uses descriptive statistical analysis with data processing using multiple linear regression tests and a non-probability sampling technique of purposive sampling. The sample in this study amounted to 325 respondents. The results of the study prove that content has a positive and significant effect on interest in online recruitment where tcount is 3.725 > 1.967, usability has a positive and significant effect on interest in online recruitment where t-count is 5.353 > 1.967, additional features have a positive and significant effect on interest in online recruitment where tcount is 3.518 > 1.967, and the three variables of content, usability and additional features have a positive and significant simultaneous effect on interest in online recruitment where the F-count is 29.291 > F-table 2.63. The results of this research are expected to be a reference for companies to be able to continue to improve and maintain the use of information technology in recruitment methods, as well as for readers to be able to use the Linkedin application as an application that makes it easier to find job.